2014
DOI: 10.2105/ajph.2014.302131
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Condom Use Among Black Male Youths: A Randomized Controlled Trial

Abstract: This brief intervention, delivered as part of STI clinical care, could help alleviate the disproportionate STI-HIV burden among young Black men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…Following completion of screening (Stage 2), five studies met all the inclusion criteria: studies that tested and reported outcome measures representing aspects of condom use fit and feel. [15][16][17][18][19] Characteristics of included studies…”
Section: Resultsmentioning
confidence: 99%
“…Following completion of screening (Stage 2), five studies met all the inclusion criteria: studies that tested and reported outcome measures representing aspects of condom use fit and feel. [15][16][17][18][19] Characteristics of included studies…”
Section: Resultsmentioning
confidence: 99%
“…This practice of using multiple forms of the same outcome measure is well-established in the extant literature. 2628 Additionally, whether men had multiple partners as a “top” or as a “bottom” was assessed and coded as yes/no, with the percent indicating “yes” reported in Table 1. Finally, as a marker of sexual risk behaviors we also tested for Chlamydia or gonorrhea.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, evidence-based interventions applied to promote the correct, as well as the consistent use of, condoms may be as efficacious as PrEP. [39][40][41] It is noteworthy that the most recently published study on condom effectiveness against HIV acquisition among MSM provided a 70% effectiveness rate for persons using condoms consistently. 42 The study, however, did not correct for lack of correct use among those using condoms consistently, thereby creating bias towards the null.…”
Section: Dual Use Of Prep and Condomsmentioning
confidence: 99%
“…weekends only) and the expense of PrEP makes its use impractical during times when MSM do not have anal sex, the option of condom use (either fully or as a supplement to PrEP) must be delivered as a practical alternative or companion practice to PrEP, and clinics should consider using evidence-based counselling programs that promote the correct and consistent use of condoms in a sex-positive context. 40 This same ethic of dual use should also be applied to future PrEP delivery strategies that may be sexual-activity dependent.…”
Section: Dual Use Of Prep and Condomsmentioning
confidence: 99%